Ooh too Complex

Algebra Level 2

Let z 1 = 6 + i z_1 = 6+i and z 2 = 4 3 i z_2 = 4-3i .
Let z z be a complex number such that arg ( z z 1 z 2 z ) = π 2 \text{arg}\left(\dfrac{z-z_1}{z_2-z}\right)=\dfrac{\pi}{2} , and z ( 5 i ) |z-(5-i)| = m \sqrt{m} .

Find m . m.


Details and Assumptions :

  • arg ( x ) \text{arg}(x) is the argument of x x .
  • z 1 , z 2 , z_1,z_2, and z z are complex numbers.


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Daniel Liu
Dec 24, 2014

Let Z = z Z=z , Z 1 = z 1 Z_1=z_1 , and Z 2 = z 2 Z_2=z_2 be three points on the complex plane.

Since arg ( z z 1 z 2 z ) = π 2 \text{arg}\left(\dfrac{z-z_1}{z_2-z}\right)=\dfrac{\pi}{2} , then Z 1 Z Z 2 = 9 0 \angle Z_1ZZ_2=90^{\circ} .

Thus, the locus of Z Z is on the circle with diameter Z 1 Z 2 Z_1Z_2 .

We are trying to find the distance from 5 i 5-i to Z Z . However, note that 5 i = Z 1 + Z 2 2 5-i = \dfrac{Z_1+Z_2}{2} . Thus, this is the center of the locus of Z Z , and we are simply trying to find the radius of it.

Since Z 1 Z 2 = 2 2 + 4 2 = 2 5 Z_1Z_2=\sqrt{2^2+4^2}=2\sqrt{5} , then the radius of the locus is 5 \sqrt{5} and our answer is 5 \boxed{5}

Good solution :).😃

Parth Lohomi - 6 years, 5 months ago

superb solution .

Aritra Jana - 6 years, 5 months ago
Aman Sharma
Dec 24, 2014

Let:-

z = x + i y z=x+iy

Since a r g ( z z 1 z 2 z ) = 0 arg(\frac{z-z_1}{z_2-z})=0 it must lie on imaginary axis hence R e z z 1 z 2 z = 0...... ( 1 ) Re\frac{z-z_1}{z_2-z}=0......(1)

Putting the values of z , z 1 , z 2 z,z_1,z_2 in equation (1) gives:-

R e ( x 6 ) + i ( y 1 ) ( 4 x ) i ( y + 3 ) = 0 Re\frac{(x-6)+i(y-1)}{(4-x)-i(y+3)}=0

Rationalizing the above equation give and setting real part of above equation equal to zero yeilds:-

( x 6 ) ( 4 x ) ( y 1 ) ( y + 3 ) ( 4 x ) 2 + ( y + 3 ) 2 = 0 \frac{(x-6)(4-x)-(y-1)(y+3)}{(4-x)^2+(y+3)^2}=0

Multiply both sides by denominator and simplify:-

x 2 + y 2 10 x + 2 y + 21 = 0...... ( 2 ) x^2+y^2-10x+2y+21=0......(2)

Also:-

z 5 + i = ( x 5 ) + i ( y + 1 ) |z-5+i|=|(x-5)+i(y+1)|

= x 2 + y 2 10 x + 2 y + 26 = x 2 + y 2 10 x + 2 y + 21 + 5 = 5 =\sqrt{x^2+y^2-10x+2y+26} = \sqrt{x^2+y^2-10x+2y+21+5} = \sqrt{5}

Mircea Rusu
Apr 20, 2018

Let z = a + bi

Z = z z 1 z 2 z = a + b i 6 i 4 3 i 6 i = ( a 6 ) + ( b 1 ) i 2 4 i = 1 2 ( a 6 ) + ( b 1 ) i 1 + 2 i Z = \frac{z-z_1}{z_2-z} = \frac{a + bi - 6 - i}{4-3i-6-i} = \frac{(a-6) + (b-1)i}{-2-4i}=-\frac{1}{2}\frac{(a-6) + (b-1)i}{1+2i}

Multiply with 1-2i above an below we get

Z = 1 2 [ ( a 6 ) + ( b 1 ) i ] ( 1 + 2 i ) 3 Z = -\frac{1}{2}\frac{[(a-6) + (b-1)i](1+2i)}{-3}

Z = 1 6 [ ( a + 2 b 8 ) + ( 2 a + b + 11 ) i ] Z = \frac{1}{6}[(a+2b - 8) + (-2a+b+11)i]

a r g Z = π 2 = θ arg Z = \frac{\pi}{2} = \theta

Z = r ( cos θ + i sin θ ) Z = r (\cos \theta + i\sin \theta) Z = r ( cos π 2 + i sin π 2 ) Z = r (\cos \frac{\pi}{2} + i \sin \frac{\pi}{2}) Z = r i Z = r i

We now have a + 2 b 8 = 0 a + 2b - 8 = 0 2 a + b + 11 = 1 -2a + b + 11 = 1

With solutions a = 6 , b= 1 and z = 6 + i

z ( 5 i ) = ( a 5 ) 2 + ( b + 1 ) 2 = 1 2 + 2 2 = 5 | z - (5 - i)| = \sqrt{(a-5)^2 + (b+1)^2} = \sqrt{1^2 + 2^2} = \sqrt{5}

so m is 5 \boxed{5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...